Kitasatospora acidiphila sp. nov., isolated from pine grove soil, exhibiting antimicrobial potential. Issue 10 (14th October 2020) - Kim, Min Ji; Roh, Su Gwon; Kim, Min-Kyeong; Park, Changwoo; Kim, Seil; Kim, Seung Bum
Abstract : A polyphasic study was carried out to establish the taxonomic position of an acidophilic isolate designated MMS16-CNU292 T (=JCM 32302 T ) from pine grove soil, and provisionally assigned to the genus Kitasatospora . On the basis of 16S rRNA gene sequence similarity, the strain formed a novel evolutionary lineage within Kitasatospora and showed highest similarities to Kitasatospora azatica KCTC 9699 T (98.75 %), Kitasatospora kifunensis IFO 15206 T (98.74 %), Kitasatospora purpeofusca NRRL B-1817 T (98.61 %) and Kitasatospora nipponensis HKI 0315 T (98.42 %), respectively. Strain MMS16-CNU292 T possessed MK-9(H6 ) and MK-9(H8 ) as the major menaquinones, and a major amount of meso -diaminopimelic acid in the cell-wall peptidoglycan. The whole-cell hydrolysates were rich in galactose, glucose and mannose, and the polar lipids mainly consisted of diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylinositol, phosphatidylglycerol and phosphatidylinositol mannosides. The major fatty acids were anteiso-C15 : 1 -A, anteiso-C15 : 0, and iso-C15 : 0, and the DNA G+C content was 71.5 mol%. The strain exhibited antibacterial activity against a number of bacterial strains, and the activity was generally greater when grown in acidic conditions. The phylogenetic, chemotaxonomic and phenotypic properties enabled distinction of MMS16-CNU292 T from related species, and thus the isolate should be recognized as a new species of the genus Kitasatospora, for which the name Kitasatospora acidiphila sp. nov. (type strain=MMS16-CNU292 T =KCTC 49011 T =JCM 32302 T ) is proposed.